Anaphylaxis-like reaction to anti-BRAF inhibitor dabrafenib confirmed by drug provocation test. Issue 1 (February 2019) - Seremet, Teofila; Haccuria, Amaryllis; Lienard, Danielle; del Marmol, Véronique; Neyns, Bart
Abstract : The combination of BRAF and MEK inhibitors is a standard therapeutic option for patients with metastatic melanoma with BRAF-mutated tumors. This type of targeted therapy improved patient survival, having a manageable toxicity profile. Nevertheless, potentially life-threatening severe toxicity as anaphylaxis-like reactions was observed in two reported cases. No confirmatory testing was performed for these two patients. We report a case of anaphylactic reaction to the BRAF inhibitor dabrafenib administered as a first-line treatment. The clinical picture is different compared with the reported cases, with the main life-threatening symptom being severe hypotension. An important feature of our case report is the diagnostic assessment by drug provocation test, which is considered the 'gold standard' investigation for the diagnosis of drug hypersensitivity. Additionally, serum tryptase levels were assessed, and the basophil activation test has been performed as an in-vitro diagnostic test. Elements in favor of both IgE-mediated and non-IgE-mediated reaction were observed, which is suggestive of a complex pathomechanism. This can be evocative for the heterogenous clinical manifestation of the immediate hypersensitivity reactions to BRAF inhibitors. The mechanisms responsible for the reactions should be investigated in future molecular and cellular studies.